Restorative dental treatment in times of COVID-19 - Robson de Lima GOMES; Marlus da Silva PEDROSA; Claudio Heliomar Vicente da SILVA (RGO: Revista Gaúcha de Odontologia, 2020)
ABSTRACT Since the outbreak of the Coronavirus Disease 2019 (COVID-19), caused by the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), numerous restrictive measures have been adopted by governments of different countries. The return to elective dental care in Brazil is a reality even during the COVID-19 pandemic. During restorative dental procedures, the dental professional requires close contact with the patient, being exposed to contaminated saliva and fluids. In addition, transmission of COVID-19 by the generation of aerosol produced by dental handipieces may be possible. Thus, the dental staff must know how to act during restorative dental procedures, putting into practice the correct clinical protocols to avoid cross-contamination and COVID-19 spread. The purpose of this article is to review the literature on the biosafety practices especially in the context of restorative dental procedures in times of COVID-19.